2013
DOI: 10.1111/ijac.12126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postdensification Annealing on Microwave Dielectric Properties of Ba([Mg1−xCox]1/3Nb2/3)O3 Ceramics

Abstract: Effects of postdensification annealing on microwave dielectric properties of Ba([Mg1−xCox]1/3Nb2/3)O3 ceramics have been investigated. The 1:2 ordered complex perovskite structure is obtained in the entire composition range of the as‐sintered samples, and the ordering degree decreases with increasing x. With increasing x, the dielectric constant (εr) increases, the temperature coefficient of resonant frequency (τf) shifts toward negative and can be tuned to near‐zero for x = 0.6, while the Q × f value decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, the unstable control of the B-site ordering degree limits the improvement in Q values. A Lot of research has focused on the replacement of B' ion to modify the dielectric parameters, such as Mg 2+ , Zn 2+ , Ni 2+ [12,13]. These elements can be added to form solid solutions with good dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unstable control of the B-site ordering degree limits the improvement in Q values. A Lot of research has focused on the replacement of B' ion to modify the dielectric parameters, such as Mg 2+ , Zn 2+ , Ni 2+ [12,13]. These elements can be added to form solid solutions with good dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the price of Ta 2 O 5 has increased nowadays. The cost and limited resources of Ta have spurred the search for alternative materials like Nb‐analog, such as ZnNb 2 O 6 , Ba(Zn 1/3 Nb 2/3 )O 3 (BZN), Ba(Mg 1/3 Nb 2/3 )O 3 (BMN), and etc .…”
Section: Introductionmentioning
confidence: 99%
“…In many complex perovskites, generally, the cation order–disorder transitions have played an important role in phase stability and, of course, dielectric response . Many strategies have been made to improve the degree of B‐site cation ordering of Ba(B′ 1/3 B″ 2/3 )O 3 , such as controlled sintering/annealing, nonstoichoimetry, substitution of appropriate ions, and etc .. For instance, the ordering parameter increases with slight Mg‐deficiency in BMN, and reaches its maximum as x = 0.02, where the Q × f value was improved to 96 000 GHz . However, although the effect of cation ordering on the improvement of Q in Ba(B′ 1/3 B″ 2/3 )O 3 has long been discussed, the addressed viewpoints still remain conflicting, and high Q × f values could also be obtained in disordered BMT‐based ceramics .…”
Section: Introductionmentioning
confidence: 99%
“…However, the postdensification annealing process is always sluggish, and it is usually not desired in the commercial applications . Tamura et al .…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9 However, the postdensification annealing process is always sluggish, and it is usually not desired in the commercial applications. 13,14 Tamura et al showed that this problem could be overcome through minor additions of BaZrO 3 , typically less than 5 mol%, which obviously reduced the annealing time to less than 10 h. 15 Higher Qf values were obtained with the reduced processing time in both Ba(Zn 1/ 3 Ta 2/3 )O 3 and Ba(Mg 1/3 Nb 2/3 )O 3 systems by introducing small amounts of BaZrO 3 . The high Qf values of these ceramics were attributed to the stabilization of the orderinginduced domain boundaries by partial segregation of Zr.…”
Section: Introductionmentioning
confidence: 99%